Tantangan Dan Solusi Dalam Implementasi Undang-Undang Perlindungan Konsumen Terhadap Produk Palsu - Agustini, Sri; Parlindungan S, Gokma Toni; Efendi, Syafril; Pamulyadi , Pamulyadi (Journal of Global Legal Review, 2024)
Counterfeit products, which negatively impact consumer health, safety, and finances, have become a serious issue in Indonesia. Despite the enactment of Law No. 8 of 1999 on Consumer Protection, its implementation still faces several challenges. These challenges include weak oversight, consumers' limited understanding of their rights, and inadequate coordination between law enforcement agencies. This study employs a qualitative method, utilizing literature analysis and case studies. Interviews were conducted with legal experts, business actors, and consumer protection agencies to understand the challenges faced and explore potential solutions to enhance the effectiveness of the law’s implementation. The data was analyzed descriptively to identify patterns of challenges and applicable solutions. The findings indicate that the primary challenges in implementing the Consumer Protection Law are the lack of synergy between relevant institutions, low public legal awareness, and limited resources for product monitoring. Proposed solutions include strengthening the capacity of oversight institutions, broad consumer education, and stricter law enforcement through collaboration between the government, private sector, and civil society. More effective implementation is expected to reduce the circulation of counterfeit products and improve consumer protection in Indonesia.